Design and analysis of class-E power amplifier - Khoo, Fatt Seng. (2011)
In this paper, based on the specification assigned, I have designed a low voltage Class-E Power Amplifier (PA) using the 0.18μm TSMC CMOS technology from BSIM3 model to achieve the following results: